ISLAMIC EDUCATION IN INDUSTRIAL REVOLUTION 4.0 ERA: Considering Fazlur Rahman’s Thought about Islamic Education Modernization - Maulana, Imron (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2020)
Islamic education always intersects with the movement of dynamic times. Islamic education is currently in the industrial revolution 4.0 era. which involves industrial competition. With cyber-based, this competition makes Islamic education at a crossroads. This article efforts to express the thought of Islamic education by considering Fazlur Rahman’s thought and its relevance to education in the industrial revolution 4.0 era. With the descriptive-analysis method, this article shows that Fazlur Rahman is concerned about strengthening the education system and strengthening the quality of Islamic education output through the renewal of Islamic education. Islamic education must be able to answer the needs in modernity, because surviving the old tradition is an intellectual suicide process, so that it is relevant to the industrial revolution 4.0 era.[Pendidikan Islam selalu bersinggungan dengan gerak zaman yang dinamis. Pendidikan Islam saat ini berada pada era revolusi industri 4.0. yang melibatkan persaingan industri. Dengan berbasis cyber, persaingan ini membuat pendidikan Islam berada pada persimpangan jalan. Artikel ini berupaya mengungkapkan pemikiran pendidikan Islam Fazlur Rahman dan relevansinya dengan pendidikan di era revolusi industri 4.0. Dengan metode analisis-deskriptif, artikel ini menunjukkan bahwa Fazlur Rahman memerhatikan penguatan sistem pendidikan serta penguatan kualitas output pendidikan Islam melalui pembaharuan pendidikan Islam. Pendidikan Islam harus mampu menjawab kebutuhan zaman, karena bertahan pada tradisi lama merupakan proses bunuh diri intelektual, sehingga ia relevan dengan era revolusi industri 4.0]